Exercise rehabilitation for cancer related fatigue: home or gym based?. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Watson, Max; Dunwoody, Lynn; Payne, Cathy
Abstract : Background: As people live longer the number living with and beyond cancer is increasing. Due to the after effects of disease and treatments many individuals who survive cancer do not enjoy the same quality of life as the general population. The aftercare for this population is largely biomedical in orientation, focusing on monitoring and surveillance of recurrence. However, research highlights the importance of well-being and the use of exercise rehabilitation in the management of CRF. Objectives: The Back on Track (BoT) 8 week pilot service for patients with CRF, evaluated the feasibility of providing an individually tailored exercise rehabilitation programme based on evidence gathered from multiple trials into the use of rehabilitation interventions for CRF. Method: Individuals who had completed cancer treatment were recruited from the membership of the Ulster Cancer Foundation. A holistic baseline assessment of the 18 participants was carried out at the Health and Rehabilitation Sciences Research Institute (HRSRI), University of Ulster. A personalised 8 week exercise programme was agreed with each participant. 12 participants chose to partake of a home-based aerobic and resistance training programme with weekly telephone support and six chose an additional weekly exercise programme at the HRSRI. On completion the initial assesments were repeated. 17 of 18 participants completed the baseline and follow up assessments. Results: Significant improvements were noted in the 6 min Walk Test (6MWT), the Fatigue VAS, the FACT-F, the Beck Depression Inventory, the BORG scale post 6MWT, Triceps skin-fold thickness and timed sit to stand. These improvements were achieved in both the home based and gym supported groups. A change in lean body mass was noted. Conclusion: An 8 week home-based exercise rehabilitation programme with or without weekly gym based activity makes significant improvements to both physical and psychosocial outcomes in patients with CRF.